The reality of educational transformations for primary school students under the Corona pandemic from the point of view of school principals in the Northern Jordan Valley - Alsmairat, Mohammad Mahmoud Hilal (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of educational transformations for primary school students in light of the Corona pandemic from the point of view of school principals in the Northern Jordan Valley. A number of (35) principals in the Northern Jordan Valley were chosen intentionally, and the study reached the following results: the results of the interviews of the respondents showed that the educational relations were limited and transformed from the school system with its elements to the home system with its elements, and to the transfer of the process of receiving the educational authority From administrators and teachers in the school to parents and older brothers at home, and because of the shift in the spatial presence and the abolition of the role of the director and the teacher as an educational process and its transfer to the educational platforms that came during the Corona pandemic, the educational burden and follow-up became entrusted to a very high rate estimated at (80%). As the student’s dependence on himself and his parents, and in light of the results of the study, the researcher made several recommendations for the need to conduct more studies and research Related to the educational reality and its transformations in light of the Corona pandemic at other age and educational stages, and the need to think of solutions to students’ problems resulting from their confinement to educational platforms and their lack of mixing with their peers.
Keywords: educational transformations; primary school students; the Corona pandemic; school principals; Northern Jordan Valley Brigade